Implementasi Program Imtaq dalam Pembentukan Sikap Toleransi Peserta Didik - M. Zaki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
The aims of this research are gaining deep understanding and describing the planning, implementation, and effect of Imtaq program in forming students’ tolerant attitude at SMPN 2 Mataram. The research method used was qualitative method, especially case study one. Data collection technique used were participative observation, indepth interview, and documentation. The procedure of analyzing data used interactive model with the channel of: data reduction, data presentation, and conclusion/verification. The research results are: (1) Planning of imtaq program utilizes system approach with societal participatory mechanism; (2) Imtaq program is implemented through the forming of religious culture, religious extracurricular activity and by developing societal participation; (3) Imtaq program has positive impacts on the development of students' tolerant attitude, this is indicated by: knowing and respecting, appreciating and tolerating those who believe in other religions, caring and helping, and willing for cooperation.